2015
DOI: 10.1242/jcs.175539
|View full text |Cite
|
Sign up to set email alerts
|

Focal-adhesion-independent integrin-αv regulation of FAK and c-Myc is necessary for 3D skin formation and tumor invasion

Abstract: Integrins play crucial roles in epithelial adhesion, proliferation, wound healing and cancer. In the epidermis, the roles of many integrin subunits are incompletely defined and mechanistic details regarding their functions are lacking. We performed a multiplexed small hairpin (sh)RNA screen to define roles for each subunit in human organotypic skin. We show that integrin-αv (also known as ITGAV) heterodimers are essential for epidermal generation, with integrin-αv loss driving a keratinocyte G1-S cell cycle bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 86 publications
2
55
0
1
Order By: Relevance
“…To establish these tissues, primary keratinocytes were seeded into a native human dermal matrix, and allowed to proliferate and stratify for 10 days at the air-liquid interface. 6,[28][29][30] We have previously used this approach to show that human keratinocytes require integrin av to maintain the capacity to both proliferate in culture, and to regenerate stratified epidermis. 6 However, inducible genetic av depletion in established mature epidermis has no obvious deleterious effect.…”
Section: Results Av Integrins Are Necessary For Organotypic Wound Reementioning
confidence: 99%
See 4 more Smart Citations
“…To establish these tissues, primary keratinocytes were seeded into a native human dermal matrix, and allowed to proliferate and stratify for 10 days at the air-liquid interface. 6,[28][29][30] We have previously used this approach to show that human keratinocytes require integrin av to maintain the capacity to both proliferate in culture, and to regenerate stratified epidermis. 6 However, inducible genetic av depletion in established mature epidermis has no obvious deleterious effect.…”
Section: Results Av Integrins Are Necessary For Organotypic Wound Reementioning
confidence: 99%
“…6,[28][29][30] We have previously used this approach to show that human keratinocytes require integrin av to maintain the capacity to both proliferate in culture, and to regenerate stratified epidermis. 6 However, inducible genetic av depletion in established mature epidermis has no obvious deleterious effect. 6 This suggested that av may be required for wound reepithelialization, but may be dispensable for normal epidermal tissue maintenance.…”
Section: Results Av Integrins Are Necessary For Organotypic Wound Reementioning
confidence: 99%
See 3 more Smart Citations